MANUSIA SEJATI DALAM FALSAFAH MBAH MARIDJAN DAN ABDUL KARIM AL-JILLI (Studi Konsepsi Manunggaling Kawula Gusti dan Insan Kamil) - Baharuddin, M (Universitas Islam Negeri Raden Intan Lampung, 2013)
The theory of spiritual journey between Mbah Maridjan and Abdul Karim al-Jilli departed from the same starting point, which is a question of how human beings to be perfect? This paper up- raise the figure and ideas of Mbah Maridjan that appears in the middle of situation about an identity crisis and existential crises, which tend to be materialists. Through a comparative study based on the philosophy, the authors found that Mbah Maridjan, the Javanese and Islamic wisdom, was capable of providing answers that humans can be perfect if they have the will to continue to find identity though exploring the spiritual sense (sabawa rasa) that in the terminology of Abdul-Karim al Jilli-called spiritual potential (ru>hiyyah-rabba>ninyyah), and constancy against human desires. Therefore, the final goal that a man will go is unity with the Almighty God (Manunggaling Kawula Gusti). These level can only be achieved by the perfect man (Insa>n Ka>mil).